INVESTIGATING THE X GRADE STUDENT OF SMK DIPONEGORO DEPOK YOGYAKARTA CHALLENGES IN WRITING RECOUNT TEXT - Cahwa Juliana C.A; Daniel Ari Widhiatama (Sean Institute, 2023)
The aim of this long research process was to identify students' abilities in writing recount texts and to find out the difficulties students faced in writing these texts. The method used in this research is descriptive qualitative method. There were 22 class X students of SMK Diponegoro Depok, Sleman, Yogyakarta who were selected as the research sample and were selected voluntarily for collection purposes. There are two instruments used in this study, namely the student written test. To analyze the data, the researcher identified the students' internal errors in the students' reconnaissance writing test which were categorized according to Jacobs et al. (1981). The results showed that the students' ability to write recount texts was in the poor category, with an average score of 54-25. However, according to the results of the data, students experienced some difficulties in writing recount text essays. The results of the analysis show that students make the most mistakes in terms of language use, spelling, mechanics, and content with an average score of 4-5 and are categorized as very bad. knowledge in grammatical form. Therefore, to overcome this problem, students must learn to write more because their skills in using language and mechanics are still low and teachers must provide more opportunities for students to practice writing and develop strategies, media and learning methods. which focuses on aspects of the use of language and mechanics that will improve students' abilities, especially in writing recount texts.